DIVERSI CONCEPT IN COMPLETION OF CHILDREN'S CRIMINAL CASE - Nisfawati Laili Jalilah (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2019)
Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop, and participate optimally by human dignity and dignity, and get protection from violence and discrimination. Related to this, in resolving child criminal cases, the Criminal Justice Act (UUPPA) emphasizes that the concept of Restorative Justice or Diversity must be used, namely the transfer or transfer of the judicial process to an alternative process of settlement of the case, namely through deliberation or mediation. The purpose of diversion is to prevent children from detention, avoiding labeling children as criminals, preventing the repetition of criminal acts committed by children, so that children are responsible for their actions, carrying out interventions needed for victims and children without having to go through a formal process. Avoiding children from following the justice system process, and keep children from the negative influence and implications of the justice process.Implementation of application of diversion in the juvenile criminal justice system is carried out at the level of investigation, prosecution, and case examination in district courts. The diversion process is carried out through deliberation by involving children and their parents/guardians, social counselors, and professional social workers based on a restorative justice approach. The results of the Diversion agreement can take the form of, inter alia; peace with or without compensation, restitution in the event of a victim, medical and psychosocial rehabilitation, participation in education or training at an educational institution or LPKS no later than 3 (three) months; or community service for a maximum of 3 (three) months.